ANALISIS KEPUASAN PELANGGAN RESTORAN BUKIT RANDUDI BANDAR LAMPUNG - Helmita -; Koriyangga - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2020)
Product and service quality is a determinant of the level of satisfaction obtained by the customer after making a purchase and the use of the product to buy back or not. Bukit Randu Restaurant also serves dishes and drinks with a variety of menus. Customers are the parties who play an important role in assessing the quality of products and food and beverage services.The results of data analysis were obtained; product quality variable, service affect the consumer satisfaction of Bukit Randu Bandar Lampung Resto by 83.34%.Product quality and service partially have a positive effect on customer satisfaction. The quality of products and services together has a positive influence on customer satisfaction in Bukit Randu Bandar Lampung restaurant.